Impact of fructooligosaccharides and probiotic strains on the quality parameters of low-fat Spanish Salchichón - Bis-Souza, Camila V. [UNESP]; Pateiro, Mirian; Domínguez, Rubén; Penna, Ana L.B. [UNESP]; Lorenzo, José M.; Silva Barretto, Andrea C. [UNESP] (Elsevier, 2020)
The substitution of dietary fiber and probiotic strains to reduce fat content of fermented sausages has been used for the development of innovative and healthier meat products. For this study, pork back fat was partially replaced by fructooligosaccharides (FOS) and the probiotic strains Lactobacillus paracasei and Lactobacillus rhamanosus. The fat replacement resulted in a significant decrease (P ≤.05) in fat content (29%) compared with the control formulation (no fat substitution). The addition of FOS did not have a significant effect on microbial counts; however, reductions in Enterobacteriaceae and yeast were observed when Lactobacillus strains were also incorporated. The inclusion of FOS and probiotic strains did not show any significant effect on lipid oxidation and proteolysis. The partial fat replacement and the addition of Lactobacillus rhamanosus GG as probiotic strain in Spanish Salchichón can be considered a successful reformulation strategy for the meat product market.
Keywords: Fat substitutes; Fermented meat product; Functional; Healthy; Prebiotic fiber